(untitled) (Czech Journal of International Relations, 1967)
In March 1966, he gave a lecture on the topic "On the Laws of Development of socialism as a social institution and world system" head of the relations department among the socialist countries of the Institute of Economics of the World Socialist System in Moscow, filoso A. A. Butén ko. He critically evaluated the views that he claims that the laws of the development of socialism in an individual country are identical to the laws of the development of the world socialist system. Some economists are of the opinion that this is only a land expansion of the already known laws of the development of socialism, such as the law of planned and proportional development, the law of constant increase in labor productivity, etc., which at most operate in a somewhat altered form within the world socialist system. Such a simplified concept appears in the works of some Soviet authors, such as G. A. Deborin, M. E. Ajrapetyan, S. D. Sergeev, I. S. Ikonnikov, A. A. Kujbysev, L. I. Lukin, N. I. Ivanov. In his opinion, the council’s stimulating works on relations between socialist countries are due to this incorrect concept.